Peritonitis and catheter exit-site infection in patients on peritoneal dialysis at home - Ana Cristina Freire Abud; Luciana Kusumota; Manoel Antônio dos Santos; Flávia Fernanda Luchetti Rodrigues; Marta Maria Coelho Damasceno; Maria Lúcia Zanetti (Universidade de São Paulo, 2015)
Objective: to analyze the complications related to peritonitis and catheter exit-site infections, in patients on peritoneal dialysis at home.Method: quantitative and cross-sectional study, carried out with 90 patients on peritoneal dialysis at home, in a municipality in the Northeast region of Brazil. For data collection, it was used two structured scripts and consultation on medical records. Descriptive analysis and comparison tests among independent groups were used, considering p<0.05 as level of statistical significance.Results: by comparing the frequency of peritonitis and the length of treatment, it was found that patients over two years of peritoneal dialysis were more likely to develop peritonitis (X²=6.39; p=0.01). The number of episodes of peritoneal catheter exit-site infection showed association with the length of treatment (U=224,000; p=0.015).Conclusion: peritonitis and catheter exit-site infection are associated with the length of treatment.